Zagęszczenie wiewiórki pospolitej na terenie Arboretum w Rogowie i wykorzystanie przez nią obcych gatunków drzew - Krauze-Gryz, Dagny; Gryz, Jakub; Mazur, Kinga (Leśne Prace Badawcze, 2016)
The aim of the study was to compare the densities of red squirrel ( Sciurus vulgaris ) in the arboretum and a neighbouring forest and to investigate which tree species the squirrels used. The study was conducted in the area of the Rogów arboretum (53.76 ha) and the so-called Zimna Woda and Wilczy Dół forest complexes (altogether 536 ha), all being part of an Experimental Forest Station in Rogów. The density of squirrels in the arboretum and the neighbouring forest was estimated and compared by means of snow tracks on transect routes. Changes in the abundance of squirrels throughout one year as well as their behaviour were determined on the basis of direct observations along transects running through the arboretum. More than half of the area of the arboretum was searched in order to record feeding signs of squirrels. Additionally, trees with bark-stripping were recorded. The density of snow tracks was higher in the arboretum (0.19 tracks/100 m/24 h) than in the neighbouring forest (0.09 tracks/100 m/24 h). The largest number of observations of red squirrels along transects was made between February and April, in July and August and in October and November. In about half of the cases, squirrels were feeding on one of six non-native tree species (most often on cones of Macedonian pine, Pinus peuce ). Feeding signs were found on 39 plots (17%) and 16 different tree species. The most numerous feeding signs were found on plots with Douglas fir ( Pseudotsuga meziesii ), but also on plots with the western hemlock ( Tsuga heterophylla ), Swiss pine ( Pinus cembra ), mountain silverbell ( Halesia monticola ) as well as shagbark ( Carya ovata ) and shellbark hickories ( C. laciniosa ). On eight plots, trees with signs of bark-stripping were found, most commonly on Sawara cypress ( Chamaecyparis pisifera ). Its soft bark was probably used to build dreys. In the area of the arboretum, the natural food sources (seeds of native trees) are supplemented with numerous non-native tree species, which seeds are also consumed by squirrels. The highly abundant and diverse food sources promote a higher density of the red squirrel in the area of the arboretum. Additionally, when tree seeds are scarce in the neighbouring forest, squirrels migrate into the arboretum.